Comparison Between Zero Point and Zero Suffix Methods in Fuzzy Transportation Problems - Pukky Tetralian Ngastiti; Bayu Surarso; Sutimin Sutimin (Jurnal Matematika MANTIK, 2020)
Transportation is discussing the problems of distribution items from a source to a destination with an aim to minimize transportation costs. The problem of fuzzy transport is the cost of transportation, supply, and demand with a quantity of fuzzy. The purpose of the research is a study of a comparison of theories from the zero-point method and the zero-suffix method in determining the optimal solution on cost transportation. Based on the result of the theoretical comparison, it can be concluded that the process of using the zero-suffix method is shorter in determining an optimal solution in 6 steps than that of a zero-point method in 11 steps. For achieving the optimal value shows that for zero-suffix the method of occurrence iteration in the sixth step, but for the zero-point method the iteration occurs in the ninth step. The results in the numerical comparison we conclude the distribution cost using two methods is the same, based on the demand and supply obtained 7 times iteration and 7 items allocation for zero point method, while 6 times iteration and 7 items allocation for zero suffix method.